How negative factors influence youth hostel say aftermath COVID-19 pandemic - Gong, Yue; Gong, Qian; Yu, Jongsik; Wong, Philip Pong Weng*; Wang, Lei (Elsevier, 2024)
The bookings and revenues of youth hostels have significantly decreased because of the multiple effects of the COVID-19 pandemic. It is necessary to investigate young consumers' perceptions of visiting youth hostels aftermath this pandemic. The current study examines the relationship between multi-dimensions of perceived risk, three types of images, willingness to pay and visit intention. A convenience sampling was developed where 534 questionnaires were received, followed by subsequent empirical testing of the proposed hypotheses using SPSS and AMOS-SEM. Results showed that perceived risk negatively influenced cognitive and affective image, respectively. Cognitive and affective image positively influenced overall image and finally influenced willingness to pay and visit intention separately. In addition, cognitive image positively influenced affective image. The theoretical framework satisfactorily accounted for willingness to pay and intention, and our results help youth hostels practitioners invent efficient strategies to boost young consumers' willingness to pay and intention to visit youth hostels.